Understanding Business Management Strategies in Enhancing Profitable and Sustainable SMEs - Sabil Sabil; Arifin Djakasaputra; B.M.A.S. Anaconda Bangkara; Sardjana Orba Manullang; Prasetyono Hendriarto (Politeknik APP Jakarta, 2022)
The purpose of this research was to get deeper undestanding on management of SMEs to win profitable and sustainable business. The publication of books, journal, and websites were become the main sources of the data that we got electronically. Because of this reason, several literatures related to profitable business strategies have been carefully studied to understand superior and sustainable governance and business strategies. The literature included is the electronic literature such as books and scientific articles. After reviewing and obtaining the valid answers, we discussed them carefully. Finally, we find several business management strategies to increase the profitability and sustainability of SMEs such as strategies to attract customers, continue to use various promotional methods, seek to increase subscriptions, add new items, and increase discounts.